Operation Energy Consumption Study on Reel and Polyethylene Tube of a New Hard Hose Traveler - Xu, Zhengdian; Li, Hong; Jiang, Yue; Xiang, Qingjiang; Tang, Pan (Frontiers in Energy Research, 2022)
To solve the problems of higher energy consumption and lower intelligence of traditional hard hose travelers, a new hard hose traveler with the function of electric drive and self-propelled is developed in this paper. The operational energy consumption of a reel and a polyethylene tube is an important part of hard-hose traveler energy consumption. In this paper, based on the JP50-180 hard hose traveler, the required pulling force and energy consumption at the reel and tube operation are theoretically and experimentally obtained. The aforementioned provides support for reducing energy consumption in the future. The influencing factor that affects the energy consumption of the reel rotation is the tube length, and the influencing factors that affect the energy consumption of the tube sliding are the ground slope, soil moisture content, and tube length. A calculation model for the dynamic change of the pulling force and energy consumption of the reel and tube operation is proposed in this study. Through theoretical analysis, maximum pulling tension and cumulative energy consumption requirements for the for reel rotation are 278.6 N and 15120.83 J, respectively. Furthermore, the requirements for the tube sliding are 1372.86 N and 123,456.96 J. Through test analysis, the maximum pulling tension for the tube sliding is between 1258.3 N and 1773.3 N, while the maximum pulling tension for reel rotation is 285.05 N. Under the same influencing factors, the deviation rates between theoretical and testable energy consumption for the reel rotation and tube sliding are 2.3 and 8.3%, respectively. The pulling force and cumulative energy consumption required for the reel rotation and tube sliding both increase with an increase in their influencing factors. The operating costs of the tube one-time unrolled are approximately 0.0185 CNY. Combined with the mobile resistance of the electric tracked vehicle, the power configuration of this new hard hose traveler is provided by two servo motors with a power of 5500 W each.